Ikhtilaf Ulama Kontemporer: Eksistensi Zakat Profesi Di Era Modern - Ika Atikah; Ending Solehuddin; Ahmad Hasan Ridwan; Hadiat Hadiat (STAI Al-Mas'udiyah, 2024)
Ikhtilaf or differences of opinion among scholars related to professional zakat are important topics in the context of contemporary Islamic law. Professional zakat, known as zakat on income from professional work, emerged along with the development of the modern economy which introduced various new professions. In the modern era, income earned from professions such as doctors, lawyers, and company employees is considered to be subject to zakat as a form of social and religious responsibility. However, contemporary scholars have different opinions regarding the provisions and laws of professional zakat, especially related to nisab (the threshold of wealth that must be zakati), the time of payment, and the type of income that must be subject to zakat. This article examines the various views of contemporary scholars regarding the existence of professional zakat in the modern era, as well as its legal and social implications for Muslims. The purpose of this study is to understand the dynamics of scholarly efforts regarding professional zakat and how these differences can be accommodated in the zakat legal system in the modern